Therapeutic effectiveness of biosimilar standard interferon versus pegylated interferon for chronic hepatitis C genotypes 2 or 3 - Vigani,Aline Gonzalez (2012)
BACKGROUND: Pegylated interferon (Peg-IFN) and standard interferon (IFN) play a significant role in the treatment of hepatitis C virus (HCV) infection. Biosimilar standard IFN is widely available in Brazil for the treatment of HCV infection genotypes 2 or 3, but its efficacy compared to Peg-IFN is unknown. OBJECTIVE: To compare the sustained virological response (SVR) rates following treatment with biosimilar standard IFN plus ribavirin (RBV) versus Peg-IFN plus RBV in patients with HCV genotypes 2 or 3 infection. METHODS: A retrospective cohort study was conducted in patients with HCV genotypes 2 or 3 infection treated with biosimilar standard IFN plus RBV or with Peg-IFN plus RBV. SVR rates of the two treatments were compared. RESULTS: From January 2005 to December 2010, 172 patients with a mean age of 44 +/- 9.3 years were included. There were eight (4.7%) patients with HCV genotype 2 infections. One hundred fourteen (66.3%) were treated with biosimilar standard IFN plus RBV, whist 58 (33.7%) patients were treated with Peg-IFN plus RBV. Between the two groups, there were no significant differences regarding age, gender, glucose level, platelet count, hepatic necroinflammatory grade, and hepatic fibrosis stage. Overall, 59.3% (102/172) patients had SVR. In patients treated with Peg-IFN plus RBV, 79.3% (46/58) had SVR compared to 49.1% (56/114) among those treated with biosimilar standard IFN plus RBV (p = 0.0001). CONCLUSION: In patients with HCV genotypes 2 or 3 infection, a higher SVR was observed in patients receiving Peg-IFN plus RBV related to patients treated with biosimilar standard IFN plus RBV.